The effect of Tempering to the Hardness and Tensile Strength of Bolting Material ASTM A 325 Grade 3A - SARAGIH (NIM 13703043); Pembimbing : Husaini Ardy, Dr. Ir., ESTER
As a fastener, steel bolts not only require a high hardness, but also a high toughness. To obtain high hardness, the bolt was hardened to produce martensite structure, which is very hard and brittle. To obtain the toughness, the martensite structure shall be reheated. This heating is called tempering and is applied below the critical temperature of steel. The bolt used for this research was hexagonal structural bolt ASTM A 325 Grade 3A. The purpose of this research is to find out the effect of temperature and time of tempering to the mechanical properties, and develope a mathematical correlation. The effect of tempering process on the microstructure, such as carbide formation, carbide size and carbide morphology will also discussed. Tempering processes were conducted on nine specimens by a combination of temperatures and time. The temperatures were varied from 600, 650 to 700oC, while the times were varied from 30, 60, to 90 minutes, followed by air cooling. The hardness were examined by Vickers microhardness tester, and the microstructure were analyzed by both optical and scanning electron microscope respectively. Tensile strengths were estimated using the conversion table of ASTM A 370 standard. The increase in temperature and time of tempering has resulted in the decrease in the hardness and the tensile strength. Eventhough alloy carbides were presented, they didn't cause secondary hardening. Using the Hollomon Jaffe Parameter, it is found that the relation of tempering parameter (t and T) to the hardness (H) of the bolt is given by H = -26.94 (t + 19 ln T) + 3753, and tensile strength (TS) = -79.92 (t + 19 ln T) + 11197. Tempering at 700 oC and above shall be avoided because it will produce hardness below ASTM A 325 Grade 3A specification.